2002
DOI: 10.1038/nature01158
|View full text |Cite
|
Sign up to set email alerts
|

The HMG-CoA reductase inhibitor, atorvastatin, promotes a Th2 bias and reverses paralysis in central nervous system autoimmune disease

Abstract: Statins, 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, which are approved for cholesterol reduction, may also be beneficial in the treatment of inflammatory diseases. Atorvastatin (Lipitor) was tested in chronic and relapsing experimental autoimmune encephalomyelitis, a CD4(+) Th1-mediated central nervous system (CNS) demyelinating disease model of multiple sclerosis. Here we show that oral atorvastatin prevented or reversed chronic and relapsing paralysis. Atorvastatin induced STAT6 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
863
10
18

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,030 publications
(917 citation statements)
references
References 30 publications
26
863
10
18
Order By: Relevance
“…Recent reports have shown that statins have an attenuating role in CNS inflammation as demonstrated in the mouse EAE model [37] and by immunomodulatory effects on MS patient immune cells [38]. Interestingly, both pravastatin [39] and lovastatin [40] treatment leads to increased CD73 expression with tissue-protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that statins have an attenuating role in CNS inflammation as demonstrated in the mouse EAE model [37] and by immunomodulatory effects on MS patient immune cells [38]. Interestingly, both pravastatin [39] and lovastatin [40] treatment leads to increased CD73 expression with tissue-protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Lovastatin and atorvastatin administered prophylactically both have been reported to prevent EAE, and to reverse established EAE in affected animals. Atorvastatin dramatically inhibits class II MHC expression on central nervous system microglia in mice with EAE, which leads to decreased T cell activation (127). In addition, atorvastatin completely inhibits in vitro class II MHC expression in IFN␥-stimulated microglia; coincubation with mevalonate abrogates this effect.…”
Section: Abeles and Pillingermentioning
confidence: 94%
“…Statins dramatically altered the course of EAE, the animal model for MS, in a number of independent studies (125)(126)(127)(128). EAE is a T cell-driven disease in which animals are immunized with myelin proteins and, upon a second injection of these proteins, CD4ϩ T cells recognizing myelin antigens are activated, which leads to relapsing paralysis and central nervous system demyelination (129).…”
Section: Abeles and Pillingermentioning
confidence: 99%
“…EAE was induced as described in Youssef et al 40 in 37-39-week-old female C57BL/6 mice previously transplanted with BM from GFP + CD45.1 C57BL/6 mice at 6-to 8-week of age. Briefly, mice were immunized with 100 μg of myelin oligodendroglial glycoprotein (MOG) p35-55 in the flanks.…”
Section: Experimental Autoimmune Encephalomyelitis Inductionmentioning
confidence: 99%